Construction Labour Productivity as a Correlate of Project Performance: An Empirical Evidence for Wall Plastering Activity - Isaac Abiodun Odesola (Institute of Research and Community Outreach - Petra Christian University, 2015)
Construction labour productivity has always been believed to be associated with project performance but empirical evidence for this assertion is scarce in literature. This study aims at determining the relationship between construction labour productivity and project performance. Hence, the study evaluates: construction labour productivity, time and cost overruns in wall plastering activity of selected completed public building projects. A survey of 180 purposively sampled public building projects was conducted. Data were collected through project inventory sheet and analysed using ANOVA and Pearson Product Moment Correlation. The results indicate that there is a strong negative correlation between construction labour productivity and cost and time overruns. It also shows that there is no variation in cost and time overruns among the states in the study area. The study therefore, recommends that stakeholders in the construction industry should emphasis the use of productivity improvement strategies on building sites to enhance project performance.